Pengaruh lingkungan usaha, profitabilitas, dan penegakan hukum terhadap ketidakpatuhan wajib pajak orang pribadi di kec. Kuantan tengah - Yuli Triya Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the effect for business environment, profitability, and compliance enforcement against an individual taxpayer carries on business in the district. Central Kuantan. The sampling method using purposive sampling technique for better, researchers took a sample of 134 respondents using Slovin formula calculation. This study used quantitative methods, where data obtained by distributing questionnaires to registered taxpayers in Rengat STO. Statistical tests using multiple linear regression analysis of data collected and processed with the help of the statistical program SPSS 17.0.From the results of the testing that has been done, found the coefficient (Adj-R2) of 0.323, this meant that 32.3% of non-compliance individual taxpayers affected by business environment, profitability and law enforcement. The independent variables in this study the profitability that has a significant impact on an individual taxpayer noncompliance. Then two independent variables other business environment and enforcement of non-compliance did not affect the individual taxpayers conducting business.Keywords: Non-compliance with individual taxpayers, business environment, profitability, and law enforcement.